2014
DOI: 10.4103/0970-9290.142536
|View full text |Cite
|
Sign up to set email alerts
|

Sodium fluoride and casein phosphopeptide-amorphous calcium phosphate cream plus sodium fluoride efficacy in preventing enamel erosion in a simulated oral environment study model

Abstract: It was concluded that tooth brushing with dentifrices with high concentration of NaF and CPP-ACPF cream was not able to prevent enamel erosion in simulated oral environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…The use of toothpaste would be the preferred mode of topical availability of CPP-ACP, as toothpastes are routinely used in oral hygiene. Accordingly, the use of MI Paste as a toothpaste in the present study is justified 21 . Studies by Wegehaupt & Attin 13 , Rallan 14 and Carvalho 11 which found similar results to our study, used the provision of CPP-ACP through the use of toothpaste, unlike the studies by Iijima 7 , Cai et al 15 , Prestes 16 and Alencar 17 in which the CPP-ACP was released on to the enamel with the use of chewing gum, which may explain the difference found in the results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The use of toothpaste would be the preferred mode of topical availability of CPP-ACP, as toothpastes are routinely used in oral hygiene. Accordingly, the use of MI Paste as a toothpaste in the present study is justified 21 . Studies by Wegehaupt & Attin 13 , Rallan 14 and Carvalho 11 which found similar results to our study, used the provision of CPP-ACP through the use of toothpaste, unlike the studies by Iijima 7 , Cai et al 15 , Prestes 16 and Alencar 17 in which the CPP-ACP was released on to the enamel with the use of chewing gum, which may explain the difference found in the results.…”
Section: Discussionmentioning
confidence: 95%
“…Several authors have shown that different lengths of exposure for acidic beverages result in very different estimates of erosive potential and that the choice of study methodology can affect the results of the study 21 . In the study by Carvalho 11 the erosive challenge was conducted for five minutes, four times a day for 5 days, similar to the present study, and both produced the same result.…”
Section: Discussionmentioning
confidence: 99%
“…Os fosfopeptídeos de caseína (CPP) contêm a sequência de peptídeos -Ser (P) -Ser (P) -Ser (P) -Glu -Glu -que possuem capacidade para estabilizar fosfato de cálcio amorfo (ACP) em solução metaestável sobressaturada 13,34,35 . Assim sendo, o CPP-ACP atua como uma fonte suplementar de cálcio e fosfato biodisponíveis no ambiente bucal 17 , sendo proposto tanto por inibir a perda de minerais 3,5 , como para intensificar sua deposição em lesões desmineralizadas do esmalte dentário, à exemplo das lesões erosivas 30 19,25,27,[43][44][45][46] . No que diz respeito aos seus mecanismos de controle da erosão dentária, o CPP-ACP pode atuar tanto na precipitação mineral 17,39 , como na redução da desmineralização da estrutura dentária 36,39 .…”
Section: Resultados O Erosãounclassified
“…Vários estudos avaliaram o poder preventivo das pastas de CPP-ACP aplicadas no esmalte previamente ao desafio erosivo, associadas ou não ao fluoreto, comparadas a diversos outros agentes protetores, utilizando protocolos de estudo distintos e enquanto alguns 3,5,40 obtiveram resultados positivos, outros 25,27,42,44,[47][48][49][50] encontraram resultados pouco favoráveis.…”
Section: Resultados O Erosãounclassified
“…The key of remineralization or regeneration of tooth hard tissue is finding an appropriate organic template and inducing the process of mineralization. The frequently used agents are fluoride [3], salivary proteins [4], casein phosphopeptide amorphous calcium phosphate [5], or organic polymers [6]. However, these approaches either call for too severe conditions to apply in clinics, or reconstruct structures unlike natural enamel.…”
Section: Introductionmentioning
confidence: 99%